2018
DOI: 10.1016/j.jspr.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Screening of chickpea accessions for resistance against the pulse beetle, Callosobruchus chinensis L. (Coleoptera: Bruchidae)

Abstract: During storage, chickpea (Cicer arietinum L.) is severely attacked by some bruchid species, especially Callosobruchus chinensis L. (Coleoptera: Bruchidae), resulting in losses in quantity and nutritional quality. In the present study, three species of Cicer including five accessions of Cicer arietinum L. (three kabuli and two desi chickpeas), four accessions of C. echinospermum P.H. Davis and five accessions of C. reticulatum Ladiz. were screened for resistance to C. chinensis in both free-choice and no-choice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Although more than 3,000 chickpea accessions were evaluated for resistance to C. chinensis at the International Center for Agricultural Research in the Dry Areas (ICARDA), no resistance was found in kabuli types. However, while some resistant desi chickpea with thick, rough or tuberculate seed coats have been identified (Reed et al, 1987), wild species such as C. echinospermum were found to be "immune" or free from damage (Eker et al, 2018). Annual Cicer species have already been screened for resistance to seed bruchid prior to the present study, and all accessions of C. echinospermum (100%), some accessions of C. bijugum (42.9%), C. judaicum (12.8%), and C. reticulatum (5%) were outlined to be free from the insect damage (Singh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although more than 3,000 chickpea accessions were evaluated for resistance to C. chinensis at the International Center for Agricultural Research in the Dry Areas (ICARDA), no resistance was found in kabuli types. However, while some resistant desi chickpea with thick, rough or tuberculate seed coats have been identified (Reed et al, 1987), wild species such as C. echinospermum were found to be "immune" or free from damage (Eker et al, 2018). Annual Cicer species have already been screened for resistance to seed bruchid prior to the present study, and all accessions of C. echinospermum (100%), some accessions of C. bijugum (42.9%), C. judaicum (12.8%), and C. reticulatum (5%) were outlined to be free from the insect damage (Singh et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Callosobruchus chinensis L. maintained at the Department of Plant Protection, Akdeniz University, Antalya, Turkey were used in a no-choice test after Erler et al (2009) and Eker et al (2018). Insect rearing was carried out with susceptible chickpea seeds at 26 ± 2 • C and 65 ± 5% RH in complete darkness.…”
Section: Screening For Resistance To the Bruchidmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty grams of seeds of each genotype were individually placed in small glass jars (500 ml) before ten pairs (♂/♀) of the newly emerged (not more than 24 h old) adults of C. maculatus were introduced. The jars were then covered with gauze cloth and perforated metal lids to allow the weevils to breathe and avoid any external contamination (Erler et al ., 2009; Eker et al ., 2018). The experiment was arranged in a completely randomized design with five replications.…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of 130 chickpea genotypes by Keneni et al (2011) in Ethiopia indicated one genotype exhibited complete resistance to adzuki bean beetle; whereas, improved genotypes showed considerably higher susceptibility particularly, in terms of number of eggs per female, adults emerged and seed weight loss. Eker et al (2018), from their laboratory experiment reported that, Desi type chickpea exhibits better resistance characteristic to callosobruchus chinensis than the Kabuli type which means the Kabuli accessions in which their seeds are characterized by creamy colored, smooth surface and ram"s shape are more preferred by the insect than the Desi type. Demissie et al (2014) screened maize varieties to sitotroga cerealla under no-choice test method showed that pratap makka-5 was found the most resistance varieties.…”
Section: Resistant Varieties For Storage Pestsmentioning
confidence: 99%